E-LIBRARY PADA SEKOLAH DASAR NEGERI KUTA PASIE MENGGUNAKAN SLiMS 9 - Lusiana, Erda; Wali, Muhammad; Imilda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2022)
This research aims to discuss the E-library using the SLiMS 9 Bulian Application. In designing the Book Data Application system the author uses one of the Bulian 9 SLiMS Applications. The purpose of this writing is to find out how to use the SLiMS 9 Bulian Application so that it can make it easier to input Book data quickly and accurately. The data collection method required in this writing was obtained through library research and field research while the method used was Extreme Programming (XP). Form the discussion above it can be concluded that by using the SLiMS 9 Bulian Application Program, it can facilitate library managers in the data collection process which includes inputting book data, searching book data and preparing reports.